Use of platelet-rich plasma under autogenous onlay bone grafts - Miranda, Sandra Regina; Nary Filho, Hugo; Marques Padovan, Luis Eduardo; Ribeiro, Daniel Araki; Nicolielo, Daniela; Matsumoto, Mariza Akemi (Blackwell Publishing, 2006)
Objectives: To analyze the healing of autogenous onlay bone grafts in three different situations, focusing on the interface area.Material and methods: Sixteen rabbits underwent autogenous bone graft surgeries in the calvaria. The block bone grafts were positioned in three different situations: direct contact between bone graft and receptor bed, graft interposed by particulate bone, and graft interposed by platelet-rich plasma (PRP). After 7, 15, 30, and 60 days, the specimens were retrieved for histological and morphometric evaluation.Results: All groups healed uneventfully and presented incorporation of the grafts after 30 days. A slightly more evident new bone formation could be observed in the PRP group in the first analyzed period, and an earlier maturation of bone in the last period, although no statistically significant differences were achieved.Conclusion: the use of additional material between the bone graft and the receptor bed when using the onlay technique must be carefully considered, taking into account the size of the reconstruction and the cost/benefit relation. The addition of PRP in between autogenous bone blocks and the receptor bed did not confer significant benefit for the new bone formation and healing on the calvaria of bone of rabbits.
Keywords: autogenous bone grafts; bone graft incorporation; platelet-rich plasma